THE ANTIMICROBIAL ACTIVITY OF LIQUIDAMBAR ORIENTALIS MILL. AGAINST FOOD PATHOGENS AND ANTIOXIDANT CAPACITY OF LEAF EXTRACTS - Okmen, Gulten; Turkcan, Onur; Ceylan, Olcay; Gork, Guven (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Medicinal plants are an important source of substances which are claimed to induce antimicrobial, antimutagenic and antioxidant effects. Many plants have been used due to their antimicrobial treatments. Antimicrobial and antioxidant activities of L. orientalis have not been reported to the present day. The aim of this work was to investigate of the antimicrobial and antioxidant potentials of different extracts from L. orientalis. Materials and Methods: The extracts were screened for antimicrobial activity against different food pathogens. These bacteria include 4 Gram positive and 3 Gram negative bacteria and one fungi. The leaf extracts of plant were tested by disc diffusion assay. The MIC was evaluated on plant extracts as antimicrobial activity. In addition to, the plant extracts were tested against the stable DPPH (2,2-diphenyl-1-picryl-hydrazyl-hydrate) free-radical. Results: The acetone, ethanol and methanol extracts of L. orientalis showed maximum inhibition zone of 12 mm against Yersinia enterocolitica, Listeria monocytogenes and Staphylococcus aureus. In addition to, the methanol extract displayed a strong antioxidant activity (trolox equivalent = 2.23 mM).Conclusion: L. orientalis extracts have antimicrobial, and antioxidant potential. Our results support the use of this plant in traditional medicine and suggest that some of the plant extracts possess compounds with good antibacterial properties that can be used as antibacterial agents in the search for new drugs.